STUDY ON METAL REMOVAL PROCESS UNDER ABRASIVE RUMBLING - Alexey Victorovich Yushchenko; Mikhail Bensionovich Flek (Advanced Engineering Research)
The loose-abrasive part cutting role in the modern mechanical engineering is studied, and the manufacturing capability of the abrasive rumbling is presented. The problem of obtaining theoretical dependences describing the connection of rumbling productivity and quality with the process parameters and types of working environments is formulated. Single interaction of an abrasive particle with the working face under rumbling is considered. Dependences for determining maximum depth of the granule penetration and the metal removal at one impact of an abrasive granule are obtained. The theoretical and experimental study on the metal removal process is carried out. At that, the effect of the operation modes, properties of an abrasive particle and the processed material is considered. The experimentally tested dependence for determining metal removal under rumbling is obtained. It is concluded that the obtained theoretical dependences can be used under designing part cutting processes through abrasive rumbling.